Preparation and Characterization of Hydroxyapatite Obtained from Bovine Bones (LACCEI, 2024)
According to certain research, feedlots are a major source of unseparated solid and liquid organic wastes and residues, which contaminate the air, surface waters, and groundwater. Cattle bones are typically discarded before being fully exploited, therefore hydroxyapatite can be extracted from this bio-waste in an affordable, environmentally responsible way that adds value. The current research was carried out to examine the influence of the particle size of hydroxyapatite sintered at 1000 °C obtained from bovine bone to estimate its compressive strength and porosity in order to offer it a practical approach and enhance its long-term mechanical properties. The stoichiometry of the bovine bone powder was determined by a thermogravimetric analysis (TGA), which demonstrated that it is suitable for producing hydroxyapatite. Cleaning, boiling, drying at 150 °C, burning at 400 °C, and calcining at 900 °C were all performed on the cow bones. They were further crushed and sieved using screens of 300, 150, 75, and 53 mm aperture diameters. By uniaxially compacting specimens of hydroxyapatite powder at a pressure of 1 MPa and sintering them at 1000 °C, the specimens were created. By analyzing the sintered hydroxyapatite powders using X-Ray Diffraction (XRD) and Scanning Electron Microscopy (SEM), the powders were given a specific character. When samples with various grain sizes were evaluated, those with a grain size of 53 mm and a porosity of 44.24% had a greater compressive strength of 2.53 MPa.